SOCIAL CAPITAL AND RESOURCE MOBILIZATION DURING PANDEMIC: INSIGHT FROM JOGO TONGGO PROGRAM IN CENTRAL JAVA - Retna Hanani; Amni Zarkasyi Rahman; Yuliana Kristanto (Jurnal Analisa Sosiologi, 2021)
The impacts of the Covid19 pandemic are not only limited to the health sector. It also affects economic growth and more importantly our social fabrics. Due to its extensive impacts, governments especially in low-middle-income countries are facing tremendous challenges in mitigating covid19. In Indonesia, the government’s efforts in mitigating the impact of covid19 have been criticized for being inadequate, ineffective, and too late. The number of covid19 victims has surpassed 70,000 cases and economic growth is contracted significantly. One important element of the government’s effort during the pandemic is mobilizing social capital to support the government’s efforts. Theoretically, community-based activities and mobilization of social capital during outbreaks are positive attributes. The emergence of volunteers and mutual aid initiatives are generally considered good examples of social capital mobilization. However, this article highlights a different angle to the relationship between social capital, community-based resource mobilization, and the pandemic. Looking at the implementation of the Jogo Tonggo program in Central Java, we argue that state mobilization does not always lead to positive resource mobilization in coping with the impact of covid19. We employ discourse network analysis to examine the implementation of the Jogo Tonggo program through news from a local newspaper in Central Java. From our research, we argue that despite the ambitious vision of Jogo Tonggo, it does not appear to be the main discourse at the societal level. Moreover, much of the implementation of the Jogo Tonggo program is top-down and does not invoke a deep level of participation from the community. Keywords: social capital, resiliency, covid19, Jogo tonggo AbstrakDampak pandemi covid19 tidak hanya terbatas pada sektor kesehatan, tetapi juga mempengaruhi pertumbuhan ekonomi dan yang lebih penting adalah tatanan sosial kita. Karena dampaknya yang luas, pemerintah terutama di negara berpenghasilan menengah ke bawah menghadapi tantangan yang luar biasa dalam menanggulangi COVID19. Di Indonesia misalnya, upaya pemerintah dalam menanggulangi dampak Covid19 dikritik karena kurang memadai, tidak efektif dan terlambat. Jumlah korban covid19 telah melampaui 70.000 kasus dan pertumbuhan ekonomi menurun secara signifikan. Salah satu elemen penting dari upaya pemerintah selama pandemi adalah memobilisasi komunitas untuk mendukung upaya pemerintah. Secara teoritis aktivitas berbasis komunitas dan mobilisasi modal sosial selama wabah adalah atribut positif. Munculnya relawan dan inisiatif gotong royong umumnya dianggap sebagai contoh yang baik dari mobilisasi modal sosial. Namun, artikel ini menyoroti sudut pandang yang berbeda tentang hubungan antara modal sosial, mobilisasi sumber daya berbasis komunitas, dan pandemi. Melihat implementasi program Jogo Tonggo di Jawa Tengah, kami berpendapat bahwa mobilisasi negara tidak selalu mengarah pada mobilisasi sumber daya yang positif dalam mengatasi dampak COVID-19. Kami menggunakan discourse analysis network (DNA) untuk mengkaji implementasi program Jogo Tonggo melalui berita dari koran lokal di Jawa Tengah. Dari penelitian kami, kami berpendapat bahwa terlepas dari visi Jogo Tonggo yang ambisius, program ini tampaknya tidak menjadi wacana utama di tingkat masyarakat. Terlebih lagi, banyak pelaksanaan program Jogo Tonggo yang top down dan tidak melibatkan partisipasi masyarakat. Kata Kunci: modal sosial, ketahanan, covid19, jogo tonggo